Maximization Influence Flow Using Modified Greedy Algorithm (International Journal of Engineering and Computer Science, 2017)
: The influence maximization problem is of finding a set of seed nodes in social network through which we can maximize the spread of influence. These seed nodes can be used in online marketing so as to maximize the profit. Marketers can get particular group of customers through online market. In this paper we are modifying greedy algorithm so as to maximize results of influence maximization.